2017
DOI: 10.1038/bjc.2017.168
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling of signet ring cell colorectal cancer provides a strong rationale for genomic targeted and immune checkpoint inhibitor therapies

Abstract: Background:Signet ring cell colorectal cancer (SRCCa) has a bleak prognosis. Employing molecular pathology techniques we investigated the potential of precision medicine in this disease.Methods:Using test (n=26) and validation (n=18) cohorts, analysis of mutations, DNA methylation and transcriptome was carried out. Microsatellite instability (MSI) status was established and immunohistochemistry (IHC) was used to test for adaptive immunity (CD3) and the immune checkpoint PDL1.Results:DNA methylation data split … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 25 publications
(30 reference statements)
1
54
0
Order By: Relevance
“…The reasons for these disparate results are likely multifactorial and may relate to different molecular profiles of SC versus CA cancers. To this point, Alvi et al reported the molecular profiling of SC and noted characteristics of SC that were similar to those of the Consensus Molecular Subtypes 1 described by Guinney et al including high mutation count, microsatellite instability (MSI), CpG‐island methylator phenotype (CIMP), BRAF mutation, add immune infiltration . In turn, patients with SC may benefit from specific therapeutic approaches including immune checkpoint inhibitors …”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…The reasons for these disparate results are likely multifactorial and may relate to different molecular profiles of SC versus CA cancers. To this point, Alvi et al reported the molecular profiling of SC and noted characteristics of SC that were similar to those of the Consensus Molecular Subtypes 1 described by Guinney et al including high mutation count, microsatellite instability (MSI), CpG‐island methylator phenotype (CIMP), BRAF mutation, add immune infiltration . In turn, patients with SC may benefit from specific therapeutic approaches including immune checkpoint inhibitors …”
Section: Discussionmentioning
confidence: 71%
“…According to the AJCC staging system, while 11.8% (n = 20 007) and 14.4% (n = 24 380) of patients had stage T1 and T2, respectively, 57.2% (n = 96 864) and 16.6% (n = 28 184) patients had stage T3 and T4 disease. A total of 97 623 (57.0%) patients had no disease, 25.4% (n = 43 548) N1 disease, and 17.6% (n = 30 242) of patients had N2 disease.…”
Section: Baseline Characteristics Of Patients Undergoing Colon Resementioning
confidence: 99%
See 3 more Smart Citations